Транскордонні кластери: сутність та особливості - Козик, В. В.; Мищишин, О. Л.; Kozyk, V. V.; Myshchyshyn, O. L. (Видавництво Львівської політехніки, 2017)
Протягом останніх років учені-економісти приділяють багато уваги дослідженню шляхів вирішення проблем регіонального розвитку в умовах європейської інтеграції України та глобалізації світової економіки. Проте наявні питання щодо особливостей створення та функціонування транскордонних кластерів в Україні потребують по- дальшої розробки. Розкрито сутність поняття “кластер” і “транскордонний кластер”. Розглянуто особливості транскордонних кластерів. Досліджено роль транскордонних кластерів у розвитку регіонів.

In recent years the scientists-economists have paid much attention to the research of methods for the solution of problems of regional development under the conditions of European integration of Ukraine and globalization of the world economy. However, the existing matters concerning the features of creation and functioning of cross-border clusters require further development. The world practice shows, that over the last two decades the process of clusters formation has been developing very actively. Implementation of this approach is considered to be the best method of provision of regional economy competitiveness in Europe. Generally, according to the expert assessment, up to the present moment about 50% of economies of the leading countries of the world have been penetrated by clusterization. A lot of highly developed countries of the world as well as those, which have just begun to form their market economy, are using the cluster approach more actively while developing and regulating their national innovative programmes, as long as the clusters act as an effective instrument of improvement of competitiveness of regional and national economy, combination of their industrial, scientifictechnological and innovative potential. From this point of view, the research of essence of cross-border clusters is relevant for the study. The research of essence and peculiarities of cross-border clusters determines the setting of the following objectives: – research of various approaches to the definition of the concept “cluster”; – research of the essence of the cross-border cluster; – consideration of peculiarities of cross-border clusters; – determination of their meaning under the conditions of cross-border cooperation development. There exists a large number of definitions to the concept “cluster”, given by the national and world scientists, some of them are represented in a table 1 (author’s development). Various definitions, developed over the last twenty years, allow to come to the conclusion that there is no standard agreed definition to the notion “cluster”, however most of them emphasize the availability of geographical proximity of the companies and surrounding institutions, horizontal and vertical connections, as well as the cooperation and competitiveness between them. It is difficult to give a unified definition to this notion, as long as its conception is used in regard to different business-structures and the aims are different as well. Cross-border clusters appear to be a new form of cross-border cooperation in the presentday conditions of cross-border cooperation development between the neighboring countries. Cross-border cluster is a form of integration of independent companies and associated institutions, which are geographically concentrated in a cross-border region, specialize in various branches and are connected with common technologies and skills and complement each other, which is based on the availability of an agreed development strategy of the participants of the cluster [2]. The world practice shows that the formation of cluster structures on border territories is a key to the development of regional as well as the national economy, as long as their creation and operation promotes the improvement of competitiveness and investment attractiveness of the region, provides a high level and quality of life of the population, economic growth and stable development of the region, gives opportunities to solve social-and-economic, ecological, territorial and other problems. Processes of European integration of Ukraine and globalization of the world economy stipulate, that important strategic tasks of the national economy development are the improvement of the national competitive advantages of the native entrepreneurship, modernization of manufacture and increase of its effectiveness by means of integration of certain branches and enterprises, provision of innovations on the basis of precisely determined global and regional aspects of accession of Ukraine to the modern system of international and economic relations. These are cluster models, which might become one of the most effective means of stable development of the whole economy of the country in the present-day conditions of increase of the relevance of cross-border cooperation of Ukraine and the neighboring countries. Moreover for the Ukrainian economy not only the creation of “inner” clusters is beneficial but also the construction of cross-border clusters, which provide the improvement of competitiveness of border territories of Ukraine by means of intensive exchange of resources, technologies, realization of original businessmodels, creation of common information space and etc. The article reveals the essence of the concepts “cluster” and “cross-border cluster”. The peculiarities of cross-border clusters have been considered. The role of cross-border clusters in the process of regional development has been researched. The approaches to the determination of the essence and peculiarities of cross-border clusters, considered by the authors, will be used in further research concerning the study of clusters classification, foreign experience of their creation and operation.
Cross-border clusters: essence and features
Keywords: транскордонне співробітництво; транскордонне підприємництво; кластеризація; кластер; кластерна модель; транскордонний кластер; прикордонний та транскордонний регіон; конкурентоспроможність; cross-border cooperation; cross-border entrepreneurship; clusterization; cluster; cluster model; cross-border cluster; border and cross-border region; competitiveness; 339.944